New solar energy conversion scheme implemented using grid-tied single phase inverter - Mekhilef, Saad; Rahim, N.A.; Omar, A.M. (2000)
A new utility-connected photovoltaic inverter is presented in this paper. Simulation and implementation of the new solar energy conversion scheme has been demonstrated. The solar energy conversion unit consists of an array of solar panels, DC-DC converter single-phase inverter, and ac mains power source. The inverter converts DC power generated by the photovoltaic cells into AC power, and provides it to the load connected to the utility line, when the photovoltaic power is greater than the load; the excess power is fed to the utility line through a reverse power flow. With this new approach we can reduce the use of the power from the grid and even make a contribution to the mains supply. Simulation and experimental results are provided to demonstrate the effectiveness of the design.